Association between intraoperative hypotension during brain tumor resection and postoperative delirium: A secondary analysis of a randomized controlled trial - Yishuang Wu; Yue Ren; Shu Li; Min Zeng; Jie Wang; Muhan Li; Yuming Peng (PLoS ONE, 2025)
Objective Postoperative delirium is a common complication after neurosurgery. The association between intraoperative hypotension and postoperative delirium in the neurosurgical population is unknown. Design This is a secondary analysis of a randomized controlled study Setting Adults scheduled for elective craniotomy under general anesthesia were included in 1 study center. Participants Of 260 patients, a total of 240 participants are included for final analysis after excluding patients without intraoperative blood pressure data. The primary outcome measures The primary outcome was the occurrence of delirium within the first 5 postoperative days, assessed with the Confusion Assessment Method or a 3-minute Diagnostic interview for the Confusion Assessment Method. Results A total of 240 patients were included (median age, 45 years), and 83(35%) patients experienced postoperative delirium. Curves of lowest mean arterial pressure versus stroke incidence suggested a threshold at 65 mmHg. There was no association between duration below 65 mm Hg and postoperative delirium (odds ratio, 1.01; 95% confidence interval, 0.96, 1.06). The odds ratio for duration below 65 mm Hg for 10 minutes was 1.03 (95% confidence interval, 0.97, 1.09) adjusted by history of hypertension, age > 45 yr, tumor volume, tumor type of glioma, preoperative Mini-Mental State Examination (MMSE) >26, and dexmedetomidine infusion which were all indicated the independent risk factors for delirium. Conclusions The current results could not indicate intraoperative hypotension of mean arterial pressure lower than 65 mmHg associated with delirium after frontotemporal brain tumor resection. Trial registration ClinicalTrials.gov NCT04674241